155k views
0 votes
-(10(2)-2(8)+5(-1))​

User Yoan
by
4.9k points

2 Answers

2 votes

Answer:

1

Step-by-step explanation:

−((10)(2)−(2)(8)+(5)(−1))

= −(20−(2)(8)+(5)(−1))

= −(20−16+(5)(−1))

= −(4+(5)(−1))

= −(4+−5)

= −(−1)

= 1

- Mordancy.

User Cambunctious
by
5.2k points
5 votes

Answer:

1

Step-by-step explanation:

-(10(2)-2(8)+5(-1))​

Work from the inside out

Multiplication before addition and subtraction

-(20-16+-5)​

Add and subtraction from left to right

-(4+-5)

-(-1)

1

User Simon Dickson
by
4.4k points